L-histidine provokes a state-dependent memory retrieval deficit in mice re-exposed to the elevated plus-maze - Serafim,K.R. (2010)
The effects of L-histidine (LH) on anxiety and memory retrieval were investigated in adult male Swiss Albino mice (weight 30-35 g) using the elevated plus-maze. The test was performed on two consecutive days: trial 1 (T1) and trial 2 (T2). In T1, mice received an intraperitoneal injection of saline (SAL) or LH before the test and were then injected again and retested 24 h later. LH had no effect on anxiety at the dose of 200 mg/kg since there was no difference between the SAL-SAL and LH-LH groups at T1 regarding open-arm entries (OAE) and open-arm time (OAT) (mean ± SEM; OAE: 4.0 ± 0.71, 4.80 ± 1.05; OAT: 40.55 ± 9.90, 51.55 ± 12.10, respectively; P > 0.05, Kruskal-Wallis test), or at the dose of 500 mg/kg (OAE: 5.27 ± 0.73, 4.87 ± 0.66; OAT: 63.93 ± 11.72, 63.58 ± 10.22; P > 0.05, Fisher LSD test). At T2, LH-LH animals did not reduce open-arm activity (OAE and OAT) at the dose of 200 mg/kg (T1: 4.87 ± 0.66, T2: 5.47 ± 1.05; T1: 63.58 ± 10.22; T2: 49.01 ± 8.43 for OAE and OAT, respectively; P > 0.05, Wilcoxon test) or at the dose of 500 mg/kg (T1: 4.80 ± 1.60, T2: 4.70 ± 1.04; T1: 51.55 ± 12.10, T2: 43.88 ± 10.64 for OAE and OAT, respectively; P > 0.05, Fisher LSD test), showing an inability to evoke memory 24 h later. These data suggest that LH does not act on anxiety but does induce a state-dependent memory retrieval deficit in mice.